Seeking understanding of the textbook-based character of Finnish education. Issue 3 (27th May 2021) - Moate, Josephine
ABSTRACT: This article provides a critical exploration of the textbook-based character of Finnish educational culture. The opening section points to the need to recognize and better understand the role of textbooks in Finnish education. The next section outlines how and why textbooks have become a characterizing feature of Finnish educational culture before addressing different ways in which pupils and student-teachers are socialized into textbook-based practices of schooling. The later sections critically consider the importance of textbooks as part of Finnish education, as well as the implications for educational research, the ongoing development of Finnish education and in particular teacher education. This study suggests that a more clearly explicated understanding of text-based educational cultures is needed to better understand the character of Finnish education and to broaden the lens for theorisations of, as well as practices within, education.